PEMANFAATAN HANDPHONE PADA USAHA MIKRO, KECIL, DAN MENENGAH DALAM MENINGKATKAN OMSET DI KELURAHAN ANGGUT DALAM KOTA BENGKULU - pedi riswandi; agung setio dicky; Peronik Br Sinurat (Universitas Prof.Hazairin,SH Bengkulu, 2021)
Micro, Small and Medium Enterprises (MSMEs) are the largest group of economic players in the economy, can create many entrepreneurs and open up many job opportunities which can become the business sector that contributes the most to economic development. In an effort to increase the productivity and efficiency of MSMEs, they can take advantage of Mobile Technology effectively to have a direct influence on MSMEs. The positive influence on MSMEs can enjoy the various benefits of using mobile phones. Where MSMEs can communicate quickly, increase productivity, build new business opportunities, and they can also connect to a wider global network. The use of mobile phones can be done using social media to improve service quality and expand customer networks. Mobile can also help MSMEs in saving operational costs. The use of mobile phones at MSMEs is currently supported by the availability of infrastructure such as internet connections at competitive prices between operators and internet providers, as well as security in transactions through communication networks. Facing an increasingly open and competitive market mechanism, market control is a prerequisite for increasing competitiveness, one of which can be done by utilizing the use of mobile phones in Micro, Small and Medium Enterprises (MSMEs).